2001
DOI: 10.1006/bbrc.2001.4733
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Effects of a High-Energy-Yielding Diet on the Regulation of Specific White Adipose Tissue Genes

Abstract: White adipose tissue development is regulated by many factors, including the energy content of food and the genetic background. Nevertheless, little is known about possible differential effects of high-fat palatable diets when fed for short or long-time periods. Thus, the expression of certain genes involved with lipid metabolism (peroxisome proliferator-activated receptor gamma, PPAR␥2; retinoic receptors; fatty acid binding protein, aP2 and uncoupling proteins, UCP) may be affected by those dietary manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
3
15
1
1
Order By: Relevance
“…44) In addition, because aP2 facilitates intracellular mobilization of free fatty acids, 45,46) and free fatty acids are known to be natural PPARg2 agonists, a possible association among PPARg2, UCP3 and aP2 in the white adipose tissue has been suggested. 47) Supporting these reports, the results of this study indicate that the expression levels of PPARg2, aP2, UCP2 and UCP3 genes are positively correlated, and that these four genes are regulated towards the same direction by the experimental diets in the visceral fat tissue. Epididymal mRNA levels of these genes decrease in response to an HFD (vs. an ND) and increase in response to an HFD+JCE (vs. an HFD).…”
Section: Discussionsupporting
confidence: 83%
“…44) In addition, because aP2 facilitates intracellular mobilization of free fatty acids, 45,46) and free fatty acids are known to be natural PPARg2 agonists, a possible association among PPARg2, UCP3 and aP2 in the white adipose tissue has been suggested. 47) Supporting these reports, the results of this study indicate that the expression levels of PPARg2, aP2, UCP2 and UCP3 genes are positively correlated, and that these four genes are regulated towards the same direction by the experimental diets in the visceral fat tissue. Epididymal mRNA levels of these genes decrease in response to an HFD (vs. an ND) and increase in response to an HFD+JCE (vs. an HFD).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, MARGARETa et al (9) found also a statistically significant correlation between FABP (ap2), UCP3 and PPARy mRNA levels in white adipose tissue from control and obese animals.…”
Section: Figi Effect Of the Cafeteria Diet On Heart Gene Expressionmentioning
confidence: 69%
“…Subsequently, at day 35, a delayed response characterized by the establishment of an obese metabolism was observed [24], with the animals showing hyperglycemia, hyperinsulinemia and insulin resistance. In accordance to this, Cav-1 and IR are no longer activated.…”
Section: Discussionmentioning
confidence: 99%